(untitled) (African Journal of Biomedical Research, 2023)
The species among rodents that are pests have been identified as those that are highly destructive pest species which inflict serious damage to food produce while some are carriers of zoonotic diseases. However, they also play vital ecological roles in the ecosystem as they aide in soil mixing and aeration, serve as dispersal agents and prey-base for predatory species. Studying the food preferences of the rodent species could help in their effective management. Sampling of small mammal species (rodents and insectivores) was carried out in six selected vegetations between 2019 and 2021, within the University of Ibadan premises. Ten (10) snap traps were set for three (3) consecutive nights per month for 24 months in each sampling site. Seven species of rodents were encountered which include Cricetomys gambianus, Arvicanthis niloticus, Rattus rattus, R. norvegicus, Lemniscomys striatus, Funisciurus anerythrus, and Crocidura olivieri. The stomach contents of the snap-trapped species were removed and analysed to know their food preferences. The diets of all the snap trapped rodent species contained vegetable matters but in varying percentage. Cricetomys gambianus had the highest mean wet (6.76 ± 1.58) and dry (4.97 ± 1.20) content weights. Diet diversity was highest in C. gambianus (7.63) in F. anerythrus (2.82) but the difference in the diet diversity of the species showed no statistical significance (p˃0.05). The vegetable matters which form one of the major diets of the captured species indicates their preferences for plant matters and these could be used as a bait or delivery medium for natural products of rodenticidal and/or abortifacient potential